O „małym Polaczku” Stefana Żeromskiego i „prawdziwej Polsce” Karola Irzykowskiego – prywatny wymiar polskości w obliczu Wielkiej Wojny - Niewiarowsa, Joanna (Załącznik Kulturoznawczy, 2023)
The article summarizes and compares the two biographical texts by writers who are difficult to compare in terms of aesthetics and political-ideological dimension − fragments of journals by Karol Irzykowski devoted to illness, death and remembrance of his daughter Basia and biographical memory of the dead of tuberculosis son Adam by Stefan Żeromski. The comparative perspective of both narratives of loss is present in their reflection on Polishness, increased in the circumstances of World War I.The analysis and interpretation shows that bearing witness to such a difficult personal existential experience paradoxically involves the necessity of re-positioning in and to Polishness. The memory of Adam Żeromski is subordinated to the social perspective, frame of collective memory, which makes it understandable why in Żeromski’s story he is the ‛little Poleʼ, and Basia is the subject to psychological and individual memory, collected memory, so she can be called the great Poland. In this sense, both texts are the edia of culture of remembrance, which inherently clarifies and determines the experience of the Great War that seems to confirm the researchers’ diagnsis of a breakthrough significance of the period 1914–1918, also in the perspective of Polish identity.